Stapled anastomosis versus hand-sewn anastomosis of gastro/duodenojejunostomy in pancreaticoduodenectomy: A systematic review and meta-analysis. (December 2017) - Hajibandeh, Shahin; Hajibandeh, Shahab; Khan, Rao Muhammad Asaf; Malik, Sohail; Mansour, Moustafa; Kausar, Ambareen; Subar, Daren
Abstract: Background: Controversy exists regarding the best anastomotic method for pancreaticoduodenectomy (PD). We aimed to evaluate the perioperative outcomes of PD with stapled anastomosis (SA) versus hand-sewn anastomosis (HA) of gastrojejunostomy or duodenojejunostomy. Methods: We conducted a systematic search of electronic information sources, including MEDLINE; EMBASE; CINAHL; the Cochrane Central Register of Controlled Trials (CENTRAL); the World Health Organization International Clinical Trials Registry;ClinicalTrials.gov ; ISRCTN Register, and bibliographic reference lists. We applied a combination of free text and controlled vocabulary search adapted to thesaurus headings, search operators and limits in each of the above databases. Delayed gastric emptying (DGE), postoperative pancreatic fistula (POPF), anastomotic bleeding, anastomotic leak, intra-abdominal abscess and mortality were defined as the outcome parameters. Combined overall effect sizes were calculated using fixed-effect or random-effects models. Results: We identified 1 randomised controlled trial (RCT) and 5 observational studies reporting a total of 890 patients who underwent PD with SA (n = 300) or conventional HA (n = 590). Our analysis demonstrated that SA significantly reduced postoperative DGE (OR: 0.37, 95% CI 0.25–0.54, P < 0.00001) but significantly increased anastomotic bleeding (OR: 13.4, 95% CI 2.96–57.41, P = 0.0007) compared to HA. No significant difference was found in POPF (OR: 0.83, 95% CI 0.56–1.21, P = 0.33); anastomotic leak (OR: 0.50, 95% CI 0.09–3.79, P = 0.58); intra-abdominal abscess (OR: 1.39, 95% CI 0.71–2.70, P = 0.34); or mortality (RD: −0.01, 95% CI 0.03–0.02, P = 0.65) between two groups. Conclusions: Our analysis demonstrated that compared to conventional HA, SA may be associated with lower incidence of DGE after PD without increasing the risk of clinically significant POPF, anastomotic leak or mortality. However, it is associated with higher rate of anastomotic bleeding which mandates careful and precise haemostasis of the stapled line. Considering the current limited evidence, no definitive conclusion can be drawn. Future research is required. Highlights: Stapled anastomosis may reduce risk of delayed gastric emptying after pancreaticoduodenectomy. It does not increase the risk of clinically significant postoperative pancreatic fistula, anastomotic leak or mortality. However, it is associated with higher rate of anastomotic bleeding. The best available evidence comes mainly from heterogeneous observational studies. High level evidence is required to provide stronger evidence on the optimal anastomotic method for pancreaticoduodenectomy.